Competencia en Información aplicada a los discentes de la Facultad Unb Planaltina: Desafíos e integración de las acciones bibliotecaria y docente - Santos, Rafael Barcelos; Simeão, Elmira Luzia Melo Soares; Nascimento, Fernanda Regina [UNESP] (My University, 2016)
The article approaches the Information Literacy (CoInfo) as a discipline. Though the case study method, the qualitative and descriptive research reports the experiences and actions of the librarian and teacher in the scope of the discipline Tópicos Especiais em Biblioteconomia e Ciência da Informação: Competência em Informação para a iniciação científica, offered in the campus of the Faculdade UnB Planaltina/FUP, as an integral part of the CoInfo training program of the Universidade de Brasília (UnB). It presents the main contents directed to the development of CoInfo in undergraduate students of the FUP courses, based on the demands and the informational needs of this academic community. As a result, it demonstrates the coverage of the discipline taught over in five uninterrupted semesters. It concludes that the discipline is strategic in the FUP, because the Institutional Pedagogical Political Plan of the campus is in consonance with the principles of CoInfo.
Competência em informação aplicada aos discentes da Faculdade Unb Planaltina: Desafios e integração das ações bibliotecária e docente
Information competence applied to students of Unb College Planaltina: Challenges and integration of library and teacher actions
Keywords: Actions of Librarian and teacher; CoInfo; Faculdade UnB Planaltina; Information literacy; Training program